Updating of Physical Education professionals with respect to the care of people with chronic hemiplegia - Taro, Lic. Joseph; Gómez Cardoso, Dr. C. Ángel Luis (Transformación, 2024)
Objective: The paper is aimed at illustrating the updated process of physical education professional working with chronic hemiplegia people, keeping in mind the difficulties described in the bibliography, the normative documents and those related to practice with those people. The objective is to argue the theoretical foundations which allow the elaboration of Physical Education professionals updating actions with respect to the care of people with chronic hemiplegia. Methods: The starting point was to construct a theoretical framework to devise the training actions. These actions were later accessed by means of a course organize at the city of Nouna, in Kossi province, Burkina Faso. Results: The findings proved the need of training to reach qualitatively superior outcomes characterized by its humanistic nature. Conclusions: The actions suggested for training physical education professionals are based on a sound knowledge on chronic hemiplegia, improving practice on the basis of research, communicating with parents or relatives, articulating theory and practice and organizing physical and sportive activities as pedagogical process.